1996
DOI: 10.1128/jb.178.23.6952-6959.1996
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the CysG protein catalyzes the first reaction specific to B12 synthesis in Salmonella typhimurium, insertion of cobalt

Abstract: The cysG gene of Salmonella typhimurium is involved in synthesis of both cobalamin (B 12 ) and siroheme (a cofactor required for SO 3 2؊ and NO 2 2؊ reductases). The failure to reduce SO 3 2؊ leads to cysteine auxotrophy, for which the enzyme is named. Although Escherichia coli does not synthesize B 12 de novo, it possesses a very similar CysG enzyme which has been shown to catalyze two methylations (uroporphyrinogen III to precorrin-2), ring oxidation (precorrin-2 to factor II), and iron insertion (factor II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Moreover, K. pneumoniae can anaerobically biosynthesize vitamin B 12 . Comparative genomic analysis revealed that the genes involved are KPN_03184 to KPN_03200 (10,39). Meanwhile, reactions belonging to incomplete pathways were removed from the reconstruction.…”
Section: Metabolic Network Reconstructionmentioning
confidence: 99%
“…Moreover, K. pneumoniae can anaerobically biosynthesize vitamin B 12 . Comparative genomic analysis revealed that the genes involved are KPN_03184 to KPN_03200 (10,39). Meanwhile, reactions belonging to incomplete pathways were removed from the reconstruction.…”
Section: Metabolic Network Reconstructionmentioning
confidence: 99%
“…1). The CysG protein performs the two methylation reactions first, making the intermediate tetrapyrrole (dihydrosirohydrochlorin) available as a substrate for B 12 biosynthesis (4,24,27,28). We postulate that the CysF protein may first reduce, or insert iron into, Uro-III thereby preventing its flux into the B 12 biosynthetic pathway; alternatively, the CysF protein may perform only a single methylation, which may yield a product capable of functioning in NirBD but not competent for B 12 biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation functions of CysG are catalyzed by the C-terminal portion of the enzyme; proteins homologous to this domain perform methylation of Uro-III and other tetrapyrroles (20). Metal insertion appears to be catalyzed by the N-terminal portion of CysG (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the observed cobalt chelation activity might reflect a function required for corrin biosynthesis [14,20] and it…”
Section: Abbreviations Used : Adomet S-adenosyl-l-methionine ; Cysgmentioning
confidence: 99%